Integrative analysis of transcriptomics and proteomics of longissimus thoracis of the Hu sheep compared with the Dorper sheep. (November 2022) - Zhao, Liming; Li, Fadi; Zhang, Xiaoxue; Zhang, Deyin; Li, Xiaolong; Zhang, Yukun; Zhao, Yuan; Song, Qizhi; Huang, Kai; Xu, Dan; Cheng, Jiangbo; Wang, Jianghui; et al.
Abstract: Meat quality is becoming more important for sheep breeding programs. Meat quality is a complex trait affected by genetic and environmental factors. In the present study, an integrative analysis of the longissimus thoracis tissue transcriptome and proteome was conducted to identify genes, proteins, and pathways related to meat quality in sheep. The sheep breeds Hu and Dorper were considered. These breeds were compared for the differences in muscle fiber structure, chemical composition, and amino acid composition. In the Hu sheep vs. Dorper sheep comparison, 22 DEGs/DEPs showed the same mRNA and protein expression trends. These genes are associated with lipid transport, lipid metabolism, and muscular system development. Moreover, some pathways such as "lipid transport", "lipoprotein metabolic process", "Alanine, aspartate and glutamate metabolism", and "Arginine biosynthesis" were significantly enriched in this study. The reliability of the RNA-Seq results was verified by qRT-PCR. These findings provide new insights into the molecular mechanisms of meat quality in sheep. Highlights: The chemical composition and amino acid content of muscle were investigated. Measuring the morphological characteristics of the longissimus thoracis muscle fibers. RNA-Seq and Label-free were used to explore meat quality related mechanisms in sheep. qRT-PCR was performed to verify the RNA-Seq results.